A calm look at the cost of various brands of antiasthmatic drugs available in India - Mir, Shakeel Ahmad (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Asthma is an inflammatory disorder of lungs that affects people of all ages and is a significant source of morbidity and mortality worldwide. Approximately 300 million people in the world currently have asthma and there has been a concerning increases in the prevalence of this condition in recent decades. The asthma epidemic experienced by high-income countries over the past 30 years is now an increasing problem in low- and middle-income countries. Because asthma is a chronic condition, it requires continuous medical care. Failure to use appropriate drugs and comply with treatment can lead to unnecessary deaths. Higher and unaffordable drug prices are among the major reasons for non-compliance and resultant treatment failure. In the global market, the cost of drugs is highly variable. The cost of drugs plays a crucial role in patient’s care especially in developing countries. It has been observed that there is a gross variation in the cost of different brands of same generic drug. If doctors are not aware that large differences can exist in the price of medications used for the same indication, they may prescribe costly brands, which ultimately lead to non-adherence. The present study was planned to get some idea about cost differences in various brands of antiasthmatic drugs. Methods: The minimum and the maximum cost in Rupees (INR) of a particular antiasthmatic agent manufactured by various pharmaceutical companies in the same strength were noted. The cost ratio and percentage cost variation were noted for each brand. Results: This study shows that there is a noticeable variation in the prices of different brands of same antiasthmatic drug in Indian market. The highest percent cost variation (663) was found for Deflazacort 6mg tablet, followed (404) for Doxophylline 400 mg tab. Other significant percent cost variations were for: Theophylline 600 mg tab (353), Combination of Formoterol and Budesonide (122), Budesonide (103), Monteleukast 10 mg tab (93) and Deflazacort 1mg (88).The lowest percent cost variations found were for: Monteleukast 4mg tab (10), Ipratropium bromide (14) and Monteleukast 5mg tab (20). Conclusions: Since there is a significant cost variation in different brands of the same generic antiasthmatic drug, a conscientious doctor should always choose cheapest effective brand while prescribing. Asthma being a chronic illness requiring prolonged treatment, even a small cost variation can have significant economical implications.